Aesthetic management of anterior discolouration of teeth - an institution based retrospective study - POOJA, J. CHANDRA; ARIGA, DR. PADMA; JEEVANANDAN, DR. GANESH (The journal of contemporary issues in business and government, 2020)
Dental aesthetics has considerable impact on a person's confidence in a society. The darkening of the anterior teeth causes concern for adolescents due to the compromised physical appearance.The aim of the study was to assess different aesthetic treatments preferred by patients for anterior teeth discolouration in a university hospital setting .A retrospective study was carried out using case records of 76 patients who reported to the Department of Aesthetic dentistry from June 2019 to March 2020.The various methods preferred for treatment discolouration of anterior teeth were observed from the digital records and tabulated on a spreadsheet. The collected data were analysed by computer software SPSS version 21 using Chi square test indicating the level of significance. The common reasons for discolouration were fluorosis(22.4%),tobacco stains(10.5%), post root canal treatment(60,5%) , enamel hypoplasia(1.3%),traumatic injury(2.6%) and unknown reasons(2.6%) and the most common reason for discoloration was post root canal treatment(60.5%) and the treatment for management of discolouration were directing veneering(7.9%), indirect veneering(5.3%), vital bleaching(25%) and non vital bleaching(61.8%) and the most preferred treatment was non vital bleaching(61.8%). Among the age groups 18-66 male patients below the age group of 30 desired treatment for their anterior tooth discolouration compared to the other age groups. The reason for discolouration had significant association with age(p value-0.00) and no significant association with gender(p value-0.82). Regarding the treatment preferred for discolouration age had no significant association(p value-0.94) while gender had significance(p value-0.02).